Effect of Long Term Exposure to Sodium Nitrite on Gene Responsible for DNA Repair - Mirza, alaa; AL- Hiti, Sadiq (Iraqi National Journal of Nursing Specialties, 2014)
Objective: The aim of this study is to detect the effect of continuous exposure to Sodium Nitrite on 8-oxoguanine DNA glycosylase (OGG1) gene which responsible on DNA repairs. DNA repair play a major role in maintaining genomic stability when DNA exposure to damage. Genomic stability is very important for keeping body cells healthy and to prevent many types of tumor development. Many genes are responsible for this job; one of them is OGG1 gene. Methodology: In current study two groups of mice were chronically exposed to sodium nitrite for six months and eighteen months while third group was used as a control. Then sizes of OGG1 were estimated. Results: The results exhibited in the unexposed (control) mice had two different alleles for this gene while the exposed animals showed more polymorphisms and this finding is independent to the period of exposure. Conclusion obtained from this study indicated that sodium nitrite has ability to act on this gene that leads to develop more polymorphisms. Recommendations: Other research should be done in order to detect how nitrite can act on this gene